Preparation technique and antibacterial evaluation of high-absorbent composite fabrics. (March 2016) - Lin, Jia-Horng; Chen, An-Pang; Li, Ting-Ting; Ho, Tsing-Fen; Lin, Mei-Chen; Lou, Ching Wen
Better-performance wound dressing has substitute for traditional wound healing materials in medical field. This study purposes to prepare high-absorbent composite fabric by compounding Tencel®/high-absorbent nonwoven fabrics and silver nanoparticles antibacterial agent. Nonwoven fabrics with different contents of high-absorbent fibers are discussed in terms of burst property and water absorption. Antibacterial agent is formed using 10 wt% chitosan and 100 mM silver nitrate solution after reaction for 6 h. Result showed that, 30 wt% high-absorbent fibers in nonwoven fabrics had 184 N burst strength and 38 times water absorption. Swelling dynamic result displayed that nonwoven fabric absorbed water within 5 min and water absorption presented saturation condition after 10 min. SEM observations showed that blood cells were attached on the surface of fiber and fibrin was formed around the blood cell after blood absorption evaluation of high-absorbent nonwoven fabrics. Antibacterial evaluations of composite fabrics revealed obvious inhibition zone to E. coli after incorporation of 9.7 mg/mL antibacterial agent.